Safety of ERCP in patients with liver cirrhosis: a national database study - Navaneethan, Udayakumar; Njei, Basile; Zhu, Xiang; Kommaraju, Kiran; Parsi, Mansour A.; Varadarajulu, Shyam (Endoscopy International Open, 2017)
Background and aims Given the limited data on the safety of endoscopic retrograde cholangiopancreatography (ERCP) in patients with liver cirrhosis, we attempted to evaluate this question using a large national database.Methods We conducted a matched case – control study using the 2010 National Inpatient Sample database in which four non-cirrhotic controls were matched randomly for every cirrhotic patient from the same 10-year age group. We compared adverse events and safety of inpatient ERCP between patients with (n = 3228) and without liver cirrhosis (controls, n = 12 912).Results Of the 3228 cirrhotic patients, 2603 (80.6 %) had decompensated and 625 (19.4 %) had compensated disease. Post-procedure bleeding (2.1 % vs. 1.2 %, P < 0.01) was higher in patients compared to controls. On multivariable analysis, decompensated cirrhosis (adjusted odds ratio [aOR], 2.7; 95 % confidence interval [CI], 2.2 – 3.2), compensated cirrhosis (aOR 2.2; 95 %CI 1.2 – 3.9), therapeutic ERCPs (aOR 1.4; 95 % CI 1.2 – 2.1), and biliary sphincterotomy (aOR 1.6; 95 %CI 1.1 – 2.1) were independently associated with increased risk of post-procedure bleeding. Performing ERCPs in large (aOR 0.5; 95 %CI 0.4 – 0.6) and medium (aOR 0.7; 95 %CI 0.6 – 0.9) sized hospitals was associated with a decreased risk of post-procedure bleeding. Biliary sphincterotomy (aOR 1.7; 95 %CI 1.2 – 2.3) and therapeutic ERCPs (aOR 1.1; 95 %CI 1.1 – 1.3) increased the risk of post-ERCP pancreatitis, and pancreatic stent placement was associated with a decreased risk of post-ERCP pancreatitis (aOR 0.8; 95 %CI 0.7 – 0.9).Conclusions Cirrhosis (both compensated and decompensated), performing therapeutic ERCPs and biliary sphincterotomy increase the risk of post-procedure bleeding. Performing ERCPs in large and medium sized hospitals may improve outcomes.